House of stairs - Sleator, William (New York : Firebird, 2004)
Five sixteen-year-old orphans of widely varying personality characteristics are involuntarily placed in a house of endless stairs as subjects for a psychological experiment on conditioned human response.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
6.0
10-12
5-8
Keywords: Experiments -- Fiction; Orphans -- Fiction; Science fiction; Orphans -- Fiction; Science fiction; Science -- Experiments -- Fiction